2021
DOI: 10.1364/oe.421029
|View full text |Cite
|
Sign up to set email alerts
|

Quantum dot light-emitting diodes with high efficiency at high brightness via shell engineering

Abstract: Quantum dot light-emitting diodes (QD-LEDs) have made great development in the performance. However, the efficiency droop at high brightness limits their applications in daylight displays and outdoor lightings. Herein, we systematically regulate the shell structure and composition, and the results indicate that CdSe-based QDs with ZnSe interlayer and thinner ZnSeS outermost layer as emitting layers (EML) enable high-performance QD-LEDs. Accordingly, the devices exhibit peak external quantum efficiency (EQE) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…In this regard, Ba et al demonstrated a high-efficiency CdSe-based QD-LED with a ZnSe interlayer and a ZnSeS outermost layer as emitting layers through shell engineering. 105 Core-shell QDs have been synthesized by regulating the shell structure and composition such as CdSe/ZnS, CdSe/ZnSe, CdSe/ZnSe/ZnS, and CdSe/ZnSe/ZnSeS. Fig.…”
Section: Electroluminescence Devicementioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, Ba et al demonstrated a high-efficiency CdSe-based QD-LED with a ZnSe interlayer and a ZnSeS outermost layer as emitting layers through shell engineering. 105 Core-shell QDs have been synthesized by regulating the shell structure and composition such as CdSe/ZnS, CdSe/ZnSe, CdSe/ZnSe/ZnS, and CdSe/ZnSe/ZnSeS. Fig.…”
Section: Electroluminescence Devicementioning
confidence: 99%
“…Fig. 8 (a) Schematic illustration of multi-layered QD-LEDs, (b) the EQEluminance, and (c) the EQE-current density of different QD-LED types 105. …”
mentioning
confidence: 99%
“…Among the organic HTLs, poly­[(9,9-dioctylfluorenyl-2,7-diyl)- alt -(4,4′-( N -(4-butylphenyl))-diphenylamine)] (TFB) is known to have relatively high hole mobility that seems to be a good candidate used for efficient devices with inorganic electron transport layers (ZnO/ZnMgO) that also have high electron mobility. There are several reports with red, green, and blue QDs using TFB as the HTL in all-solution processed QDLEDs that achieved very high external quantum efficiency (EQE). ,, However, several factors can influence the extent of cross-linking in TFB, often limiting its resistance to solvent damage, an issue that leads to a large variability in device performance, especially stability. , So, there is a need to explore other HTLs that can circumvent these issues.…”
Section: Introductionmentioning
confidence: 99%
“…For the advancement of next-generation display and lighting applications, colloidal quantum dots (QDs) have been widely used as an emissive layer (EML) due to their excellent optical properties, such as a narrow full-width at half-maximum (FWHM), tunability of the emission wavelength, a high photoluminescence quantum yield (PLQY), and solution processability. The performance of cadmium (Cd)-based quantum dot light-emitting diodes (QLEDs) has demonstrated a peak external quantum efficiency (EQE) of over 20%, which is almost equivalent with that of the best organic light-emitting diodes. The toxicity of Cd-based QDs negatively impacts the environment; thus, alternative non-toxic cadmium-free indium phosphide (InP)-based QDs have gained increasing attention due to their environmental friendliness. Recently, great efforts have been expended to develop cadmium-free InP QLEDs, which have led to excellent QLED device performance. , However, the device lifetime and efficiency of InP-based QLEDs are still inferior compared to those of Cd-based QLEDs. , Such an inferior performance of InP-based QLEDs can be attributed to the charge imbalance in the device caused by a mismatch in electron and hole mobilities and instability of the QD materials.…”
Section: Introductionmentioning
confidence: 99%